2012
DOI: 10.5539/jas.v4n10p81
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Index for Measuring Knowledge and Adopting Scientific Methods in Treatment of Reproductive Problems of Dairy Animals

Abstract: Reproductive problems among dairy animals are one of the major causes of loss in dairy sector. These problems can be tackled by imparting appropriate knowledge to the livestock owners. An attempt was made to measure the knowledge of livestock owners by developing a knowledge test on reproductive problems of dairy animals. The study was undertaken in Karnal district of Haryana state, India. Data were solicited from 300 livestock farmers who had at least one milch animal at the time of investigation. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
1
7
0
Order By: Relevance
“…The Pharma Innovation Journal http://www.thepharmajournal.com agreement with the results of Meena (2012) [7] who reported that majority of the dairy farmers were selling milk in between 4 to 41 kg/day in Karnal district.…”
Section: Milk Salesupporting
confidence: 89%
“…The Pharma Innovation Journal http://www.thepharmajournal.com agreement with the results of Meena (2012) [7] who reported that majority of the dairy farmers were selling milk in between 4 to 41 kg/day in Karnal district.…”
Section: Milk Salesupporting
confidence: 89%
“…In this article, knowledge is defined as community familiarity or understanding, acquired through experience or education by discovering, and/or learning (Meena et al 2012). Attitude is defined as individuals' thoughts and/or expressed feelings about a specific phenomenon (Almasi et al 2019).…”
Section: Definition Of Termsmentioning
confidence: 99%
“…The third analysis stage involved the determination of a knowledge index (KI) to show participants' knowledge about different FS-derived products using a 4-point Likert scale. The KI for each FS-derived product was expressed using the mathematical equation adopted from Meena et al (2012):…”
Section: Quantitative Datamentioning
confidence: 99%
See 2 more Smart Citations